Clinical Features and Factors Affecting the Success of Retinal Vasculitis Therapy - Lia Meuthia Zaini; Arief Kartasasmita (Indonesian Vitreoretinal Society, 2020)
Introduction: Retinal vasculitis is an inflammatory eye condition that threatens vision. Inflammation occurs in the branches of retinal arteries, cause by primary ocular diseases or associated with other diseases. This study aims to describe clinical features and factors affecting therapeutic success in 52 patients with retinal vasculitis. Methods: This study was conducted using retrospective cohort in Retina Clinic of Cicendo Eye Hospital for vasculitis patients from January 1st- December 31st 2017. Data were collected retrospectively from the ophthalmic records of 52 patients (74 affected eyes). Descriptive analysis was performed on all data, chi-square and eksak fisher test were used to analyze risk factor and factors affecting the success of therapy. Result: Out of 529 vasculitis and vitreous hemorrhage cases, retinal vasculitis was found in 52 patients (9.8%). Mean age of retinal vasculitis patients were 42.3 years (range: 13-74 years). 35 patients (62.3%) were men and 22 patients (42.3%) had bilateral retinal vasculitis. Most patients (73%) had positive results for history of TORCH infections, and 23.76 % for tuberculosis. At initial presentation, almost all patients (93.2%) came with chief complaint of blurry vision, 42 patients (56.8%) came with baseline visual acuity £20/200. Vitreous hemorrhage was identified from retinal examination in 43 patients (58.1%). Therapeutic success was found better in patients with systemic involvement (74,1%). Conclusion: Despite limitation of facility in our hospital, therapeutic success rate of retinal vasculitis patients was quite good. Better laboratory investigation and other supporting examinations are still needed to obtain good therapeutic results and to conduct further study about the disease. Tuberculosis, TORCH, and autoimmune test are important examination when managing retinal vasculitis.